C.F.E. Hornemans “Aladdin” – en mishandlet opera - Sørensen, Inger (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
NB: Artiklen er på dansk, kun resuméet er på engelsk. The Danish composer C.F.E. Horneman (1840-1906) was himself of the opinion that his talent as a composer was particularly for dramatic music. And he had good reason. He began his undisputed masterwork, the opera “Aladdin”, when he was little more than 20 years old, having just returned home from studying in the music metropolis of Leipzig. He worked on the score for most of his life. There are several reasons for this. During the early years, the work proceeded well but, when Horneman’s father died in 1870, he had to put the score aside, take over their music publishing house and set about earning his living. Finally, after several failed endeavours as a concert organiser and conductor, Horneman found his place in Danish music life in 1879, as the head of his own music institute. But this took up so much of his time that he only rarely had the opportunity to compose, even though he considered this to be his main calling. It was only in 1883, when various personalities in the Danish music world, and Horneman’s friend, Edvard Grieg, arranged to have him granted a yearly state subsidy, that he was once again able to take up the “Aladdin” score. And yet it took another five years before he could submit the finished score to the Royal Theatre. Even though the sensors were satisfied with the music, Benjamin Feddersen’s libretto, based on the story from “A Thousand and One Nights”, caused problems. And so the production was shelved. Then, in the fall of 1888, the theatre decided to stage the opera at a gala performance on the occasion of Christian IX’s jubilee. This decision proved to be catastrophic for the opera. Only six weeks were allocated to rehearse this large and complicated work, resulting in various rash cuts. The opening night was a fiasco. The royal audience had no appreciation of this new Danish opera and the production left much to be desired. It was only 14 years later that Horneman achieved satisfaction, when a new, severely revised version was produced in 1902. It enjoyed full houses but, in spite of its success, the opera has never since been professionally performed in its entirety. The sheet music archived in the Royal Library clearly shows how much Horneman worked on the material from the onset. The four-volume score contains so many corrections and deletions that it could hardly be used as a production score. At the time of writing, the score from the 1888 production, which was in a terrible state of preservation, is being restored. The archived material is in such bad condition that a new, practical, scholarly version of “Aladdin” is needed if Horneman’s masterwork is to regain its rightful place in the Danish opera repertoire.